Analisis Promosi Negatif dalam Etika Bisnis Terhadap Keputusan Pembelian pada E-Commerce - Alvin Firdaus; Halimah Zahrah; Arya Pramudita; M Arsyad; Febby Setya (INDO PUBLISHING, 2025)
This study aims to analyze how marketing strategies and the implementation of business legal ethics influence consumer trust in e-commerce platforms, particularly within the context of digital marketplaces. Trust is a crucial factor in online transactions since consumers do not interact directly with sellers or products. Effective marketing strategies—such as transparent information, customer service, honest promotions, and secure transactions—can enhance consumers' positive perceptions. On the other hand, adherence to business legal ethics, including consumer protection, data privacy, and clear terms and conditions, serves as a fundamental basis for maintaining platform integrity and legality. This research uses a qualitative approach through literature studies and secondary data from relevant journals. The findings indicate that the integration of consumer-oriented marketing strategies and compliance with business legal ethics significantly increases user trust in e-commerce. This study offers essential insights for digital business actors in designing ethical and trustworthy marketing systems and business governance.